STUDY ON WATER QUALITY INDICATORS AT TAIA TREATMENT PLANT HUNDEDOARA COUNTY - Ramona Violeta CAZALBAŞU; Camelia CĂPĂŢÎNĂ; Cîrţînă DANIELA (Fiabilitate şi Durabilitate)
Water is consumed in its natural form or in a processed one. It is a well-known fact that enterprises, institutions, energy and agriculture consume it as processed water whereas the population consumes it as drinking water or wastewater. This paper presents the study of water quality indicators from the treatment plant Taia in Hunedoara County. The following quality indicators were determined: turbidity, hardness, alkalinity, chlorine oxide and organic substances. The determined quality indicators revealed that they fall within the limits set by legislation, with some exceptions. In each step of purification of organic substances there has been a continual reduction, this being carried out both biologically because of the biomass deposited on sand grains in the filter bed as well as especially during the oxidation step with active chlorine